Quantitative evaluation of fracture healing progression in rat femurs with modal damping factor and conventional methods - Chalikias, Stavros; Anastassopoulos, George; Sarris, John; Athanasopoulou, Stefania; Orkoula, Malvina; Kontoyannis, Christos; Kostopoulos, Vassilis; Psarras, Spyridon; Papaioannou, Nikolaos; Chronopoulos, Efstathios; Dontas, Ismene; Panteliou, Sofia (Frontiers in Bioengineering and Biotechnology, 2026)
Quantitative determination of bone fracture healing through objective measurements on the fracture area during healing phases is of paramount importance. In this study, simultaneous modal damping factor (MDF) testing was compared to peripheral quantitative computed tomography (pQCT), Raman spectroscopy (RS), and absorbed and fracture energy. MDF is a non-invasive index based on the model’s dynamic characteristics that applies vibration excitation. The method has been successfully applied as a structural integrity monitoring tool for defective conventional and advanced materials, including bones. We investigated whether MDF could identify when a functional and biomechanically adequately strengthened callus developed in osteotomized rat femurs. The measured property value intervals indicate that MDF correlates with all properties and detects the bone quality changes due to fracture and fracture healing with higher sensitivity than other methods. MDF monitors bone fracture healing and correlates with all parameters examined in a more accurate and sensitive way than conventional methods. Research findings support MDF as the most convenient of the methods examined for monitoring the bone fracture healing process.